Kegiatan Penunjang Pelaksanaan Usaha Kesehatan Sekolah Di SMP Negeri Se-Kecamatan Temanggung Kabupaten Temanggung (Indonesian Journal for Physical Education and Sport, 2021)
Aryo Sentiaki. 2020. Supporting Activities the Implementation of School Health Unit in Public Junior High Schools of Temanggung Subdistrict Temanggung Regency. A Final Project. Physical Education, Health and Recreation, Faculty of Sport Sciences, Universitas Negeri Semarang. Advisor: Dr. Endang Sri Hanani, M.Kes. Keywords: Supporting, Activities, Implementation of School Health Unit. The background of the problem in this study is that the implementation of the Junior High School Health Unit in Temanggung Subdistrict not maximized, required support activities that can be carried out in school. The focus of the problem is limited supporting activities on the implementation School Health Unit. The purpose of this study is to describe the supporting activities of implementation Junior High School Health Unit in Temanggung Subdistrict. This study uses a qualitative descriptive approach. The research locations cover State Junior High School 1, State Junior High School 2, State Junior High School 3, State Junior High School 4, State Junior High School 5, Temanggung State Junior High School 6. The objectives of this study: The subjects of teacher counselor UKS, teacher, student. The object of study on the supporting activities of implementation Junior High School Health Unit in Temanggung Subdistrict. The research instrument uses a human instrument, while the data collection method used interviews, direct observation, document tracking and documentation. Examination of the validity of data through triangulation. The data analysis used interactive model and that are carried out continuously, data reduction, data presentation and data verification. The results of the study concerning the supporting activities of implementation of school Heal Unit in Temanggung state Junior High School 1 supported by 6 activities in the very good category, the supporting activities of implementation of school Heal Unit in Temanggung state Junior High School 2 supported by 5 activities in the good category, the supporting activities of implementation of school Heal Unit in Temanggung state Junior High School 3 supported by 5 activities in the good category, the supporting activities of implementation of school Heal Unit in Temanggung state Junior High School 4 supported by 5 activities in the good category, the supporting activities of implementation of school Heal Unit in Temanggung state Junior High School 5 supported by 6 activities in the very good category, the supporting activities of implementation of school Heal Unit in Temanggung state Junior High School 6 supported by 6 activities in the very good category. Based on the research result and discussion, it can be concluded that the support activities of implementation of School Health Unit in Public Junior High Schools of Temanggung Subdistrict in the very good category there are 3 schools, that is state Junior High School 1, state Junior High School 5, and Temanggung state Junior High School 6. the support activities of implementation of School Health Unit in the good category there are 3 schools, that is state Junior High School 2, state Junior High School 3, and Temanggung state Junior High School 4. Based on the research result, it can be concluded that the to schools can improve patterns of cooperation with partrnership and prepare school resident as a pillar in quality human resources, so that activities can be carried out optimally.